KAJIAN KRITIK SENI: MAKNA ARTISTIK TOPENG CIREBON PADA PERTUNJUKAN TARI TOPENG CIREBON - Dwaji, Chamid Nur; Falah, Asep Miftahul (ATRAT: Jurnal Seni Rupa, 2023)
The growing awareness of sustainability has encouraged the textile industry to seek environmentally friendly solutions in production and product use. One of the natural materials that has attracted attention is hemp cloth, as it has eco-friendly properties and high durability. This study uses screen printing techniques to design sustainable home decor textiles using hemp fabric. This research method involves the stages of selecting raw materials, the process of creating designs, and implementing screen printing techniques on hemp fabrics. First, a qualitative analysis was carried out on the natural resources and environmental impact of hemp fabrics to ensure their sustainability. Furthermore, the design process takes place through the experimental stage and exploration of motifs and colors that match the desired home decor theme. The application of screen printing techniques to hemp fabrics is a critical step in this research. This technique was chosen for its efficiency in producing precise patterns with a minimal amount of staining, thereby reducing waste and environmental impact. In addition, screen printing also allows flexibility in creating unique and attractive designs for consumers. The result of this research is a collection of sustainable home decor textiles made of hemp fabric with attractive designs resulting from the screen printing technique. This collection is expected to provide alternative products that are environmentally friendly for consumers who are concerned about environmental and sustainability issues. In conclusion, this study shows that the use of hemp cloth with screen printing techniques can be a solution in designing sustainable home decor textiles. By utilizing environmentally friendly natural materials and efficient production techniques, it is expected to reduce the negative impact of the textile industry on the environment. Keywords: Hemp Fabric, Sustainable, Home Decor, Screen Printing, Textiles ------------------------------------------------------------------------------------ Perkembangan kesadaran akan keberlanjutan telah mendorong industri tekstil untuk mencari solusi yang ramah lingkungan dalam proses produksi dan penggunaan produk. Salah satu bahan alami yang menarik perhatian adalah kain rami, karena memiliki sifat ramah lingkungan dan daya tahan yang tinggi. Penelitian ini bertujuan untuk merancang tekstil sustainable home decor menggunakan kain rami dengan menerapkan teknik screen printing. Metode penelitian ini melibatkan tahap pemilihan bahan baku, proses penciptaan desain, dan implementasi teknik screen printing pada kain rami. Pertama, dilakukan analisis kualitatif terhadap sumber daya alam dan dampak lingkungan dari kain rami untuk memastikan keberlanjutannya. Selanjutnya, proses perancangan desain berlangsung melalui tahap eksperimen dan eksplorasi motif dan warna yang sesuai dengan tema home decor yang diinginkan. Penerapan teknik screen printing pada kain rami menjadi langkah kritis dalam penelitian ini. Teknik ini dipilih karena efisiensinya dalam menghasilkan pola yang presisi dengan jumlah pewarnaan yang minimal, sehingga mengurangi limbah dan dampak lingkungan. Selain itu, screen printing juga memungkinkan adanya fleksibilitas dalam menciptakan desain yang unik dan menarik bagi konsumen. Hasil dari penelitian ini adalah sebuah koleksi tekstil sustainable home decor yang terbuat dari kain rami dengan desain-desain menarik hasil dari teknik screen printing.Koleksi ini diharapkan dapat memberikan alternatif produk yang ramah lingkungan bagi konsumen yang peduli akan isu-isu lingkungan dan keberlanjutan. Kesimpulannya, penelitian ini menunjukkan bahwa penggunaan kain rami dengan teknik screen printing dapat menjadi solusi dalam merancang tekstil sustainable home decor. Dengan memanfaatkan bahan alami yang ramah lingkungan dan teknik produksi yang efisien, diharapkan dapat mengurangi dampak negatif industri tekstil terhadap lingkungan. Kata Kunci: Kain Rami, Sustainable, Home Decor, Screen Printing, Tekstil